1987
DOI: 10.3758/bf03203081
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of Weber fractions

Abstract: The Weber fraction is treated as part of an information theoretical view of perception. In this theory of sensory perception, subjective magnitude is related to the information transmissible from stimulus to perceiver. The derived psychophysical law can be approximated as a power or logarithmic law, depending on conditions. The mathematical expression for the Weber fraction is obtained as a derivative of the psychophysical law. One of many interesting relationships derived here is that the product of the Steve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(47 citation statements)
references
References 31 publications
1
45
1
Order By: Relevance
“…Research in the psychological sciences has helped to identify the empirical limits of the acuity of human sensory systems, especially our ability to perceive differences (Coren et al, 1994;Norwich, 1983;Palmer, 1988). Due to physiological constraints humans have great difficulty observing differences below certain threshold values.…”
Section: Human Perception and Errormentioning
confidence: 99%
“…Research in the psychological sciences has helped to identify the empirical limits of the acuity of human sensory systems, especially our ability to perceive differences (Coren et al, 1994;Norwich, 1983;Palmer, 1988). Due to physiological constraints humans have great difficulty observing differences below certain threshold values.…”
Section: Human Perception and Errormentioning
confidence: 99%
“…The explicit mathematical evaluation of the perceptual H-function has been done elsewhere (Norwich, 1977(Norwich, , 1987, but with the advantage of hindsight, and armed with some knowledge of the physical properties of the H-function, we can make an educated guess about its approximate mathematical structure.…”
Section: The Calculation Of Hmentioning
confidence: 99%
“…On theoretical (Norwich, 1987;Norwich, Sebum, & Axelrad, 1989) and empirical (Bonnet, 1992a(Bonnet, , 1992bWard & Davidson, 1997) grounds, it can be assumed that the parameter a of the Pieron function is specific for a given sensory modality and presumably for each receptor type. Moreover, some authors (Baird, 1970;Baird & 359 Copyright 1997 Psychonomic Society, Inc. , 1978;Link, 1992;Teghtsoonian, 1971) suggested that the exponent ofthe Stevens function would be related to discriminability, or, in other terms, to the Weber ratio.…”
Section: Brief Reportsmentioning
confidence: 99%
“…Similarities between cell latencies and reaction time (RT) to luminance suggest that this relationship may be determined by retinal processes. Ifthe exponent of the Pieron function is specific to a given sensory modality, as assumed by some authors (e.g., Bonnet, 1992aBonnet, , 1992bNorwich, 1987), it should reflect receptor activities. Consequently, functions with different exponents should fit data for different luminance ranges.…”
mentioning
confidence: 99%